The PENGARUH LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN : (Studi Kasus Pada Perusahaan Manufaktur Subsektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2023) - Ellyza Febriana; Gusganda Suria Manda (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to examine, analyze, and determine the influence of liquidity, leverage, and firm size on financial performance. The research object is manufacturing companies in the food and beverage subsector listed on the Indonesia Stock Exchange during the 2017–2023 period. A total of 92 companies were used as the population, and 21 of them were selected as samples using a purposive sampling technique. The data were analyzed using a quantitative approach through descriptive and verification analysis techniques. The data analysis model used in this study includes classical assumption tests, multiple linear regression analysis, and hypothesis testing, which consists of partial tests (t-test) and simultaneous tests (F-test). The research results show that partially, liquidity (CR) has a significant positive effect, leverage (DER) has a significant negative effect, and firm size has no significant effect on financial performance (ROA). Simultaneously, liquidity (CR), leverage (DER), and firm size have a significant effect on financial performance (ROA). Keywords: Current Ratio, Debt to Equity Ratio. Firm Size, Return on Asset